Automatic control technology of mechanical equipment based on microelectronic sensor signal control - Wei, Xiaofeng; Wei, Yi (Frontiers in Mechanical Engineering, 2025)
PurposeThis study is to provide a new method for the development of automatic control technology (ACT) of mechanical equipment and promote its wide application in industrial production, and to explore the ACT of mechanical equipment under the control of microelectronic sensor signal (MSS). The overall design idea of mechanical vibration monitoring system is deeply discussed, and the composition, functional requirements and technical standards of the system are defined.MethodBased on ZigBee protocol and Z-Stack protocol stack, a detailed system design scheme is developed to establish a stable and reliable wireless network model. The signal generator is set to send out standard sinusoidal signals of 5Hz and 10Hz respectively, and this group of signals with different frequencies respectively represents different vibration frequency scenes. The sampling frequency is set to 100Hz.ResultsThe proposed wireless monitoring system achieves a 98.7% success rate in vibration signal acquisition within the 5Hz‐10Hz frequency range. Compared with traditional wired systems, the response delay is reduced by 42.3%. In planetary gearbox fault diagnosis tests, the system reaches a 95.6% accuracy rate in identifying characteristic frequencies. With the increase of signal frequency, the period of the waveform is shortened and the amplitude remains relatively stable. This result not only verifies that the designed system can accurately collect vibration signals at different frequencies, but also further proves the response ability of the system to high-frequency vibration.ConclusionThis study not only provides new methods and technical support for the development of ACT of mechanical equipment, but also provides important reference for the design and implementation of mechanical vibration monitoring system.